2019
DOI: 10.1101/565085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A smooth muscle-like niche facilitates lung epithelial regeneration

Abstract: The mammalian lung is a highly complex organ due to its branched, tree-like structure and diverse cellular composition. Recent efforts using state-of-the-art genetic lineage tracing and single-cell transcriptomics have helped reduce this complexity and delineate the ancestry and fate of various cell subpopulations during organogenesis, homeostasis and repair after injury. However, mesenchymal cell heterogeneity and function in development and disease remain a longstanding issue in the lung field. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…This action allows ASMCs to form an airway epithelial stem cell niche that services BECs repair (62). In this aspect, Moiseenko et al reported this BECs-repair supporting ASMC population is distinct from pre-existing airway smooth muscle cells and is critical for renewing BECs of the adult lung (63). Nevertheless, in a recently published study, young et al reported that differentiation of airway smooth muscle during lung development is unnecessary for lung branching morphogenesis in mice.…”
Section: The Effects Of Airway Smooth Muscle Cells On Epithelial Cellsmentioning
confidence: 99%
“…This action allows ASMCs to form an airway epithelial stem cell niche that services BECs repair (62). In this aspect, Moiseenko et al reported this BECs-repair supporting ASMC population is distinct from pre-existing airway smooth muscle cells and is critical for renewing BECs of the adult lung (63). Nevertheless, in a recently published study, young et al reported that differentiation of airway smooth muscle during lung development is unnecessary for lung branching morphogenesis in mice.…”
Section: The Effects Of Airway Smooth Muscle Cells On Epithelial Cellsmentioning
confidence: 99%